The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3389/fpsyg.2016.01781
|View full text |Cite
|
Sign up to set email alerts
|

Combining Gender, Work, and Family Identities: The Cross-Over and Spill-Over of Gender Norms into Young Adults’ Work and Family Aspirations

Abstract: The current study investigates how descriptive and prescriptive gender norms that communicate work and family identities to be (in)compatible with gender identities limit or enhance young men and women’s family and career aspirations. Results show that young adults (N = 445) perceived gender norms to assign greater compatibility between female and family identities and male and work identities than vice versa, and that young men and women mirror their aspirations to this traditional division of tasks. Spill-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 60 publications
2
36
0
1
Order By: Relevance
“…In terms of the expectations for life course events, we saw gender differences for three events: choosing a career, and devoting energy to career advancement, and to childrearing ( Table 2). This is consistent with a traditional master narrative, as well as the normative division of labor in American households (Lindsey, 2015;Meeussen, Veldman, & Van Laar, 2016). In terms of personal experiences, men were more likely to align with a traditional master narrative, and women were more likely to align with an equality narrative.…”
Section: Brief Discussion and Introduction To Study 1bsupporting
confidence: 67%
“…In terms of the expectations for life course events, we saw gender differences for three events: choosing a career, and devoting energy to career advancement, and to childrearing ( Table 2). This is consistent with a traditional master narrative, as well as the normative division of labor in American households (Lindsey, 2015;Meeussen, Veldman, & Van Laar, 2016). In terms of personal experiences, men were more likely to align with a traditional master narrative, and women were more likely to align with an equality narrative.…”
Section: Brief Discussion and Introduction To Study 1bsupporting
confidence: 67%
“…In the case of Asian Canadians, for instance, whether it is their higher levels of social anxiety (Hsu et al, 2012), experience of lower relational mobility (Zhang and Li, 2014), or compensatory conformity to the European Canadian norm (Tafarodi et al, 2002), there are likely more than one socio-cultural factor that account for those psychological characteristics. To be sure, depending on the form of culture, being bicultural could entail juggling any two or multiple important social identities, such as being a mother and being a career woman with contrastive prescriptions for what it means to succeed (Hodges and Park, 2013; Meeussen et al, 2016). Future research could examine if a similar process to what was found here operates at the intersection of social identities that are receiving increasing attention as social change progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Meeussen, Veldman, and Van Laar (, p. 1781) revealed in their study on young adults’ work and family aspirations that ‘while young women's family aspirations were positively related to female career norms, their career aspirations were not related to female family norms’. This difference may be a result of high expectations for mothers (Johnston & Swanson, ).…”
Section: Literature Reviewmentioning
confidence: 99%